2020
DOI: 10.1177/0309324720906931
|View full text |Cite
|
Sign up to set email alerts
|

Crack kinking and tunneling simulation for the single-fiber composite under transverse tension based on phase-field method

Abstract: Virtual tests for a single-fiber–reinforced composite model subjecting to transverse tension are carried out based on a phase-field method considering a varying interface toughness parameter. Without pre-treating the crack initiation location and propagation path, the complete fracture process is realized for the first time in a three-dimensional numerical model, including nucleation cracks on the fiber/matrix interface at the free end, tunneling cracks along the fiber axis, and kinked interface crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…where s s u is the final strength of the glass fibers in the quasi-static state and s d u represents the same in the dynamic state. The c and p are constant coefficients of equation (2). The results of this study indicated a proper correlation between the modeled and experimental results.…”
Section: The Effect Of Loading Rate On the Mechanical Behavior Of Gla...supporting
confidence: 67%
See 2 more Smart Citations
“…where s s u is the final strength of the glass fibers in the quasi-static state and s d u represents the same in the dynamic state. The c and p are constant coefficients of equation (2). The results of this study indicated a proper correlation between the modeled and experimental results.…”
Section: The Effect Of Loading Rate On the Mechanical Behavior Of Gla...supporting
confidence: 67%
“…In the second step of this research, the final strength of glass fibers depended on the strain rate. To predict the final strength of glass fibers, the Cooper-Simonds model was modified to equation (2).…”
Section: The Effect Of Loading Rate On the Mechanical Behavior Of Gla...mentioning
confidence: 99%
See 1 more Smart Citation